Mobilities, belonging and territory - Arguedas Abarca, María Fernanda (2025)
Within the thematic axis “Mobilities, Belonging and Territory”, Mena, Penabad-Camacho and Rodríguez explore how adopting an intersectional gender perspective in Costa Rican institutions that serve migrants reveals structural inequalities related to gender, class, origin and migratory status, showing that migrant women—who are the majority—face barriers associated with gender norms, care burdens and labor precarity. Their study highlights the crucial role of institutional staff as bridges of support and the need for clear policies and ongoing training to ensure humanitarian and contextualized attention. Hernández, drawing on the 2024 IDESPO-UNA national survey, analyzes Costa Rican perceptions of the impact of expatriate residents—mainly from the United States, Canada and Europe—on gentrification and touristification in Guanacaste, revealing concerns about rising living costs, access to land and strong support for regulating property sales. Finally, from a historical-documentary perspective, Solano examines the structural causes behind the nineteenth-century separation of Paquera, Lepanto and Cóbano from Guanacaste, demonstrating that it was not a census mistake but rather a process tied to the coffee agro-export model and the commercial interests of Puntarenas, which ultimately reshaped territoriality and political identity in the Nicoya Peninsula.